A Development Model for Competency Improvement Support Maintenance Managers Food Processing Plant - Yangyuen, Sermsak; Wisetsri, Worakamol; Atawinijtrakarn, Preeda (Rajapark Journal, 2022)
The study’s purposes were to 1) study the key components for a development model for competency improvement for maintenance managers in food processing plants; 2) create a development model for competency improvement for maintenance managers in food processing plants, and 3) create a manual of a development model. The study was done as a mixed-method study. For the qualitative part, a semi-structured in-depth interview was used for data collection. There were 9 participants in the interview. The interview’s results were analyzed by using content analysis. For a quantitative part, its research tool was a questionnaire with a 5-point Likert scale based on the results from the semi-structured in-depth interview. The questionnaires were distributed to 329 maintenance managers in food processing plants. These managers were selected by using simple random sampling. The questionnaire’s results were analyzed for finding Frequency, Percentage, Mean, and Exploratory factor analysis was also used. The results were used to create the development model for competency improvement for maintenance managers in food processing plants and the manual of a development model for competency improvement. Then the model and the manual were evaluated by using a focus group of 13 experts. The study’s results showed that the key components for a development model for competency improvement for maintenance managers in food processing plants were: 1) electrical engineering knowledge; 2) standards in food processing plants; 3) modern technologies for industries; 4) English usage in the workplace; 5) maintenance management, and 6) leadership and decision-making.